; Agricultural policy in cotton production and the diversification of the agricultural sector in Tajikistan - Khojamahmad Umarov (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2016)
- . , -, . , , . . , ; . – – The main aim of this report is to present the recent changes in the Tajik cotton sector, and the impact of agricultural diversification on food security and export promotion. The first part provides information about the changes in the state regulation of cotton production, including the dynamics of raw cotton prices, and privatization of ginneries. The second part focuses on the transformation of major categories of agricultural producers, their contribution to agricultural output, as well as related organizational changes and challenges in the input and resource supply sectors. The last section discusses the policy issues and food security concerns that have been influencing the structure of agriculture. In this respect, the report assesses the recent reforms towards diversification of crop production, reflecting on the issues of food security and agricultural exports to new markets.
urn:nbn:de:gbv:3:2-69685
Keywords: P41; P47; Q15; Q18; 330; food policy; agricultural diversification; export potential; Tajikistan